2017
DOI: 10.3390/met7040125
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characteristics and Mechanical Properties of 2205/AZ31B Laminates Fabricated by Explosive Welding

Abstract: Abstract:A bimetal composite of 2205 duplex stainless steel and AZ31B magnesium alloy was cladded successfully through the method of explosive welding. The microstructural characteristics and mechanical properties of 2205/AZ31B bimetal composite are discussed. The interface of 2205/AZ31B bimetallic composite was a less regular wavy morphology with locally melted pockets. Adiabatic shear bands occurred only in the AZ31B side near explosive welding interface. The microstructure observed with EBSD showed a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 37 publications
5
14
0
Order By: Relevance
“…A very low pressure leads to nonbonding [30]. Experimental studies about explosive welding have come to similar conclusions, as reported in [4,32], namely nonbonding appeared near the detonation edges, which is called the boundary effect in explosive welding. The low pressure is the essential reason for the boundary effect of explosive welding.…”
Section: Pressure Distributionsupporting
confidence: 61%
See 4 more Smart Citations
“…A very low pressure leads to nonbonding [30]. Experimental studies about explosive welding have come to similar conclusions, as reported in [4,32], namely nonbonding appeared near the detonation edges, which is called the boundary effect in explosive welding. The low pressure is the essential reason for the boundary effect of explosive welding.…”
Section: Pressure Distributionsupporting
confidence: 61%
“…Figure 7 depicts the pressure-time curves of special points. Along the propagation of the detonation wave, the minimum pressure was obtained near the detonation points (Points 1 and 7), which can be attributed to the unstable energy during the initial detonation stage [4,30,31]. A very low pressure leads to nonbonding [30].…”
Section: Pressure Distributionmentioning
confidence: 98%
See 3 more Smart Citations